1996
DOI: 10.1016/0014-5793(96)00534-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ganglioside GM3 on the activity and conformation of reconstituted Ca2+‐ATPase

Abstract: Trace amounts of gangliosides were found in rabbit skeletal muscle sarcoplasmic reticulum and their main part was shown, by high performance thin layer chromatography, to be GM3. Addition of GM3 to the soybean phospholipids used for reconstitution of proteoliposomes markedly increased ATP hydrolysis as well as Ca z+ uptake activity of sarcoplasmic 2+ reticulum Ca -ATPase incorporated into the proteoliposomes. 2+Conformation changes of Ca -ATPase induced by GM3 were also observed by intrinsic fluorescence and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Two previous studies have demonstrated that exogenously added gangliosides modulate SERCA activity in rabbit sarcoplasmic reticulum (46,47), but ours is the first to show a direct physiological link between endogenous ganglioside accumulation and neuronal cell death mediated via SERCA. In the previous studies, GM1 inhibited rabbit sarcoplasmic reticulum SERCA whereas GM3 activated SERCA (47) via a mechanism that was proposed to involve the compactness of the hydrophilic and hydrophobic domains.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have demonstrated that exogenously added gangliosides modulate SERCA activity in rabbit sarcoplasmic reticulum (46,47), but ours is the first to show a direct physiological link between endogenous ganglioside accumulation and neuronal cell death mediated via SERCA. In the previous studies, GM1 inhibited rabbit sarcoplasmic reticulum SERCA whereas GM3 activated SERCA (47) via a mechanism that was proposed to involve the compactness of the hydrophilic and hydrophobic domains.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium-buffering activity of the endoplasmic reticulum (ER) is modulated by the ATPase calcium pumps (MacLennan et al, 1997;Auer et al, 1998 andZhang et al, 1998) located in the ER membrane (Miller, 1991) and by associated Ca +2 release channels (Meszaros et al, 1996;Xu et al, 1998). Evidences suggest that mutations in APP or the presenilins (PS1 and PS2) decrease calcium buffering in ER in a manner similar to that of one or several substances (Wang et al, 1996(Wang et al, , 1999Kimura et al, 1996;Liguri et al, 1996;Antipenko et al, 1999;Levine et al, 1999) known to influence it resulting in compensatory increases in other calcium pools, specifically in mitochondria. The foregoing is strongly supported by studies with cultured neurons (Guo et al, 1998(Guo et al, , 1999Mattson et al, 2000).…”
Section: Calcium Buffering Activity and Intraneuronal Fibrillary Tanglesmentioning
confidence: 95%
“…Increases in mitochondrial calcium content enhances superoxide radical formation, and in turn, the rate of aging (118). Table 6.Endoplasmic reticulum: Calcium buffering capacity is modulated by many compounds, including: 1) phospholamban (109)(110)(111) 2) the ganglioside GM1 and Gin3 (112,113) 3) 6-gingerol (114) and ellagic acid (114) 4) procaine (105), caffeine (105), thapsigargin (105), and dantrolene (105) 5) the erythrocyte isoenzyme of acylphosphatase (115) -this enzyme inhibits the Ca 2+ pump by hydrolysing the phosphointermediate formed during the catalytic cycle of the calcium ATPase.…”
Section: ) Familial Forms Of Ad (Fad) Mutations In App and Thementioning
confidence: 99%